Studying the relation between quality of life and mental distresses among Kurd seniors living in Saghez, Iran - Reza Ghanei Gheshlagh; Mohammad Frajzadeh; Bakhtyar Moslemi; Maryam Karami; Mandana Sarokhani; Mozhdeh Zarei; Kourosh Sayehmiri (Tehran University of Medical Sciences, 2017)
Background & Aim: Quality of life indicates individual's level of satisfaction or dissatisfaction with different aspects of life. One of the aspects that could affect aspects of life is mental distress. The aim of this study was to study the relation between quality of life and mental distresses Kurd seniors living in Saghez city, Iran. Methods & Materials: This research was a correlation study conducted in 2015. Samples were 300 seniors who lived in Saghez and were selected through multi-stage sampling. Data were collected using 36-Item Short Form Health Survey and Depression Anxiety Stress Scale - 21. Data were analyzed using PASW software and through descriptive statistics, independent t-test, Pearson correlation coefficient, and multiple regression analysis. Results: The results showed a negative significant correlation between the quality of life and depression (r = 0.681), anxiety (r = 0.690), stress (r = 0.586), and age (r = 0.296) (P = 0.001). Results of step-wise regression analysis for predicting seniors' quality of life based on their mental distresses showed that depression, anxiety, stress, and age, all together, determined 74.5% of changes in quality of life in seniors. Anxiety by predicting 69% of the variance of seniors' quality of life was the most powerful predictor. Conclusion: Results of the present study showed a relation between quality of life and depression,anxiety, and stress. Appropriate diagnosis and management of mental distresses not only could reduce the time of suffering from these problems, but also could improve the quality of life in seniors.